Association Between Sunlight Exposure and Mental Health: Evidence from a Special Population Without Sunlight in Work - Wang J; Wei Z; Yao N; Li C; Sun L (Dove Medical Press, 2023)
Jie Wang,1,2 Zhen Wei,1,2 Nan Yao,1,2 Caifeng Li,1,2 Long Sun1,2 1Centre for Health Management and Policy Research, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2NHC Key Laboratory of Health Economics and Policy Research, Shandong University, Jinan, People's Republic of ChinaCorrespondence: Long Sun, Centre for Health Management and Policy Research, School of Public Health, Cheeloo College of Medicine, Shandong University, 44 Wenhuaxi Road, Jinan, Shandong, 250012, People's Republic of China, Tel +86 531-88382678, Email sunlong@sdu.edu.cnPurpose: In recent years, mental health problems have become the most serious social problems worldwide. Past studies have proposed that some links exist between sunlight and mental health; however, relevant studies examining low-dose sunlight exposure populations are lacking. We conducted a study among a group of operating room nurses (ORNs) who work long hours in operating rooms and have limited sunlight exposure. We aim to add to and refine previous researches on the association between mental health and sunlight exposure in community population.Patients and Methods: A total of 787 ORNs were interviewed and analyzed. Mental health, sunlight exposure duration, sociodemographic and work-related variables, and chronic diseases were evaluated. The Kessler 10 scale (K10) was used to assess participants' mental health status, and their sunlight exposure duration was assessed using their self-reports. Multiple linear regression analysis was adopted to examine the association between sunlight exposure and mental health.Results: The average K10 score of ORNs was 25.41. ORNs exhibit poorer mental health than other populations. Poor mental health was negatively associated with greater sunlight exposure hours per day (β=− 0.378) and sleep regularity (β=− 3.341). Poor mental health was positively associated with chronic disease (β=3.514).Conclusion: This study indicated that the positive association between sunlight exposure and mental health existed. Appropriate enhancement of sunlight exposure will be beneficial to mental health. Hospitals, related organizations and individuals should pay greater attention to ORNs' mental health and sunlight exposure conditions. More policy recommendations as well as building structure recommendations should be proposed.Keywords: sunlight exposure, mental health, operating room nurses, China